Systematics of the genus Aphrophila Edwards with description of fifteen new species (Diptera: Tipulomorpha: Limoniidae) - Santos, Daubian; Ribeiro, Guilherme Cunha (Zootaxa, 2018)
The genus Aphrophila (Diptera: Limoniidae) is revised. All previously described species are redescribed and illustrated, along with fifteen new species. From the Campbell Island (New Zealand): A. whakapapa sp. n.; from Argentina: A. argentina sp. n., A. huahua sp. n. and A. peuma sp. n.; from Chile: A. aequalitas sp. n., A. alexanderi sp. n., A. dentata sp. n., A. dupla sp. n., A. edwardsi sp. n., A. minuscula sp. n., A. penta sp. n., A. regia sp. n., A. serra sp. n., A. sperancae sp. n. and A. vulcania sp. n. Identification key is provided for all the valid species. A phylogenetic analysis was made which resulted in one single most parsimonious tree with five main groups, classified into five subgenera: A. (Aphrophila) Edwards, A. (Magnodonta) subg. n., A. (Spinalia) subg. n., A. (Sirena) subg. n., A. (Zelandica) subg. n. In order to uncover the biogeographical pattern of the distribution of the species in terms of area relationships, a Paralogy-free subtree analysis was performed, which resulted in the following areagram: ((Campbell Is. + S. America) + New Zealand).